Strengthening Responsive Mechanisms for the Protection of Witnesses and Victims in the Indonesian Criminal Justice System - Kadapi, Resmen; Hasibuan, Fauzie Yusuf; Shodiq, Md. (Sahabat Publikasi, 2025)
Witness and victim protection is a vital element of the criminal justice system, yet in Indonesia it continues to face significant challenges. Although the legal framework is established under Law No. 13/2006 as amended by Law No. 31/2014, the implementation remains partial and reactive, with an emphasis on physical safeguards only. This study adopts a normative juridical approach supplemented with limited empirical inquiry to assess the effectiveness of existing mechanisms and to propose a more responsive model. The findings reveal regulatory disharmony with the Criminal Procedure Code, limited institutional capacity of the Witness and Victim Protection Agency (LPSK), and weak fulfillment of victims’ rights, including compensation and psychosocial recovery. These shortcomings contribute to secondary victimization and undermine the legitimacy of the justice system. Comparative insights from the United States, Australia, and the Philippines demonstrate that responsiveness can be enhanced through institutional innovation, early-warning mechanisms, and cross-agency coordination. This study underscores the urgent need for reform toward adaptive and comprehensive protection, while reinforcing the relevance of responsive law and victimology in ensuring substantive justice for witnesses and victims.